Commonly setting biological standards in rare diseases. (14th August 2019) - O'Connor, Daniel J.; Buckland, Jenny; Almond, Neil; Boyle, Jennifer; Coxon, Carmen; Gaki, Eleni; Martin, Javier; Mattiuzzo, Giada; Metcalfe, Clive; Page, Mark; Rose, Nicola; Valdazo-Gonzalez, Begona; et al.
ABSTRACT: Introduction : Standardization is important across the life cycle of medicinal products, supporting the diagnosis, treatment, and prevention of a wide range of diseases. For rare diseases, standardization is even more important, as patient groups are small, presenting significant challenges in the design, conduct, analysis, and interpretation of clinical studies. It is here that standardization institutions, including the UK's National Institute for Biological Standards and Control (NIBSC), can have a key role. Areas covered : A considerable proportion of NIBSC's work supports the better understanding, diagnosis, treatment, and prevention of rare diseases. NIBSC is also part of the UK's Medicines and Healthcare products Regulatory Agency (MHRA), creating an agency that is uniquely placed to combine scientific and regulatory expertize for the benefit of public health. This review provides an overview of NIBSC's work in rare diseases and highlights the positive impact of the work of standardization institutions in this field. Expert opinion : Standardization in product development is key for patients with rare diseases. The work of standardization institutions is increasingly being recognized as crucial for supporting scientific and clinical advancements, and early and collaborative interactions can provide drug developers with the necessary expertize, when standards matter most.